Influence of natural sciences on developing the professional competences of the humanities students; 11th International Technology, Education and Development Conference (INTED2017), 6-8 March, 2017, Valencia, Spain - Erofeeva G. V. Galina Vasiljevna (2017, 2017)
Title screen